ATF2 promotes urothelial cancer outgrowth via cooperation with androgen receptor signaling. Issue 12 (December 2018) - Inoue, Satoshi; Mizushima, Taichi; Ide, Hiroki; Jiang, Guiyang; Goto, Takuro; Nagata, Yujiro; Netto, George J; Miyamoto, Hiroshi
Abstract : We investigated the functional role of ATF2, a transcription factor normally activated via its phosphorylation in response to phospho-ERK/MAPK signals, in the outgrowth of urothelial cancer. In both neoplastic and non-neoplastic urothelial cells, the expression levels of androgen receptor (AR) correlated with those of phospho-ATF2. Dihydrotestosterone treatment in AR-positive bladder cancer cells also induced the expression of phospho-ATF2 and phospho-ERK as well as nuclear translocation and transcriptional activity of ATF2. Meanwhile, ATF2 knockdown via shRNA resulted in significant decreases in cell viability, migration and invasion of AR-positive bladder cancer lines, but not AR-negative lines, as well as significant increases and decreases in apoptosis or G0/G1 cell cycle phase and S or G2/M phase, respectively. Additionally, the growth of AR-positive tumors expressing ATF2-shRNA in xenograft-bearing mice was retarded, compared with that of control tumors. ATF2 knockdown also resulted in significant inhibition of neoplastic transformation induced by a chemical carcinogen 3-methylcholanthrene, as well as the expression of Bcl-2 / cyclin-A2 / cyclin-D1 / JUN / MMP-2, in immortalized human normal urothelial SVHUC cells stably expressing AR, but not AR-negative SVHUC cells. Finally, immunohistochemistry in surgical specimens demonstrated significant elevation of ATF2/phospho-ATF2/phospho-ERK expression in bladder tumors, compared with non-neoplastic urothelial tissues. Multivariate analysis further showed that moderate/strong ATF2 expression and phospho-ATF2 positivity were independent predictors for recurrence of low-grade tumors (hazard ratio (HR) = 2.956, P = 0.045) and cancer-specific mortality of muscle-invasive tumors (HR = 5.317, P = 0.012), respectively. Thus, ATF2 appears to be activated in urothelial cells through the AR pathway and promotes the development and progression of urothelial cancer.